The Implementation of Learning Assessment During The Covid-19 Pandemic on TK Islam Darussalam Palangkaraya - Riski Maulinda Sari; Rodhatul Jennah; Setria Utama Rizal (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
Learning activities during the covid-19 pandemic cannot be seen directly, so teachers are difficult to see the achievements of learning indicators. The purpose of this study is to find out the implementation of learning assessments and obstacles faced by teachers when conducting learning assessments for B1 group students during the covid-19 pandemic at TK Islam Darussalam Palangka Raya. Describing the implementation of learning assessments and obstacles faced by teachers when conducting learning assessments for B1 group students during the covid-19 pandemic at TK Islam Darussalam Palangka Raya. This study uses descriptive qualitative research method, data subjects numbered 3 people (2 teachers of group B1 and Kelapa TK Islam Darussalam). Data collection techniques using observations, interviews and documentation. The results showed that: 1) Assessment of check-up techniques and works carried out on worksheets and anecdotal record assessments were conducted through face-to-face, online and home visits. Assessment of calistung and ummi using monitoring books. The assessment process can be done well, but it cannot be carried out to the maximum.2) The lack of ability of teachers to use digital technology, online learning is sometimes constrained by network connections, worksheet learning carried out at home causes teachers to be unable to see the process of implementation and achievement of learning indicators and the duration of the learning system face-to-face, online and home visits are relatively short causing information on children's learning activities cannot be obtained to the maximum.